Republic of Poland : Financial Sector Assessment Program-Technical Note-Credit, Growth, and Financial Stability. (IMF Staff Country Reports; Country Report ;, 2007)
This technical note on the Republic of Poland underlies the country's credit, growth, and financial stability. A broad-based statistical and econometric analysis of financial and household balance sheet data implies that exchange rate-related credit risk and liquidity risk are currently contained. Supervisors need to remain vigilant to any signs of weakening in credit standards, rising loan-to-value ratios, and an excessive concentration of risk. The main objective is to ensure that all banks have adequate credit assessment and risk management systems in place and disclose sufficient information to customers.